2011
DOI: 10.1039/c1lc20082h
|View full text |Cite
|
Sign up to set email alerts
|

Optimised production of multifunctional microfibres by microfluidic chip technology for tissue engineering applications

Abstract: This paper describes a method for the production of alginate microfibres using glass-based microfluidic chips fabricated by a photolithography-wet etching procedure. The main focus of the work is the fabrication of a cell containing multifunctional microfibres which have great potential for applications in drug release formulations and tissue engineering scaffolds (to guide the regeneration of tissues in predefined sizes and shapes) providing cell structural support and immunoisolation. The key parameters, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…28 Microfluidic-based systems offer advantages over conventional bench systems in terms of performance, reduced sample/solvent quantity, automation, and fine regulation of the boundary conditions. 29,30 The micro-scale, in which fluidics is restricted to laminar flow and diffusive mixing, allows precise control of the physical parameters within the fluidic environment. In addition, coupling with microscope-based imaging techniques, provides a platform for in situ analysis of individual cells exposed to US or other physico-chemical stimuli.…”
mentioning
confidence: 99%
“…28 Microfluidic-based systems offer advantages over conventional bench systems in terms of performance, reduced sample/solvent quantity, automation, and fine regulation of the boundary conditions. 29,30 The micro-scale, in which fluidics is restricted to laminar flow and diffusive mixing, allows precise control of the physical parameters within the fluidic environment. In addition, coupling with microscope-based imaging techniques, provides a platform for in situ analysis of individual cells exposed to US or other physico-chemical stimuli.…”
mentioning
confidence: 99%
“…Microfluidic spun fibers have been formed using various polymers such as alginate (Mazzitelli et al, 2011, Su et al, 2008, Yamada et al, 2012), chitosan, poly(lactic-co-glycolic acid) (PLGA) (Hwang et al, 2009, Hwang, Khademhosseini, 2008), and chitosan/alginate (Lee, Lee, 2011a). A rotating roller can be used to collect the fabricated fibers and to form scaffolds containing aligned fibers (Hwang, Park, 2009, Hwang, Khademhosseini, 2008, Su, Zheng, 2008).…”
Section: Fiber Formation Techniquesmentioning
confidence: 99%
“…Incorporation of living cells in fibers fabricated using microfluidic spinning systems has been demonstrated by several researchers (Hwang, Park, 2009, Lee, Lee, 2011a, Mazzitelli, Capretto, 2011, Shin et al, 2007, Su, Zheng, 2008, Yamada, Sugaya, 2012). For example, Shin et al encapsulated human fibroblast cells in calcium alginate fibers and demonstrated that the cells remained viable after seven days of culture.…”
Section: Fiber Formation Techniquesmentioning
confidence: 99%
“…The channels had a semicircular cross-sectional shape so that channel width was strictly connected with channel depth, due to the isotropicity of the fabrication procedure. 34,35 The flow within the microchannels was monitored by an inverted microscope (IX51; Olympus Corporation, Tokyo, Japan). PMs were also prepared by bulk mixing.…”
Section: Fabrication Of Microfluidic Reactorsmentioning
confidence: 99%
“…34 Firstly, the channel pattern was designed by AutoCAD ® drawing software (Autodesk, Inc, San Rafael, CA), thereafter, a negative film representing the optical mask was obtained by a commercial photomask producer (JD Photo-Tools, Oldham, Lancashire, United Kingdom). Crown white glass (B-270) plates (thickness of 1.5 mM) coated with a thin layer of chromium metal mask plus an upper layer of positive photoresist (AZ 1500; Telic Company, Valencia, CA) were used for channel network fabrication.…”
Section: Fabrication Of Microfluidic Reactorsmentioning
confidence: 99%